The Young Researcher’s Guide to Creating Data Mastersheets - Chittaranjan Andrade (Indian Journal of Psychological Medicine, 2022)
Researchers who have completed a study need to transfer their data from individual patient research files to a mastersheet. This article is a beginner’s guide to creating data spreadsheets that can be shared with others and imported into statistical programs. The article discusses choice of spreadsheet software, use of separate worksheets for main data and granular data, use of columns for variables and rows for patient data, coding data, entry of data into cells in the worksheets, and other matters.